2023
DOI: 10.1186/s12890-023-02649-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and risk factors of community-acquired pneumonia complicated by parapneumonic pleural effusion in elderly patients

Mingmei Zhong,
Ruiqin Ni,
Huizhen Zhang
et al.

Abstract: Background Community-acquired pneumonia (CAP) patients usually present with parapneumonic pleural effusion (PPE), which complicates the treatment of pneumonia. This study aims to investigate the clinical characteristics and risk factors of elderly CAP patients hospitalised with PPE. Methods The clinical data of 132 elderly patients with CAP were retrospectively analysed. A total of 54 patients with PPE (PPE group) and 78 patients without PPE (NPPE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A population-based study in France found an annual incidence of complicated parapneumonic effusions and empyema of approximately 2.5 cases per 100,000 adults, representing nearly 20% of all community-acquired pneumonia cases [ 14 ]. On the contrary, up to 41% of patients who were hospitalized with pneumonia developed a parapneumonic effusion, of which 5–10% progressed to complicated empyema [ 15 ]. Regardless of the advances in therapy, Mummadi et al described a 37.5% relative increase in pleural infection-related hospitalization between 2007 and 2016 in the United States [ 16 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A population-based study in France found an annual incidence of complicated parapneumonic effusions and empyema of approximately 2.5 cases per 100,000 adults, representing nearly 20% of all community-acquired pneumonia cases [ 14 ]. On the contrary, up to 41% of patients who were hospitalized with pneumonia developed a parapneumonic effusion, of which 5–10% progressed to complicated empyema [ 15 ]. Regardless of the advances in therapy, Mummadi et al described a 37.5% relative increase in pleural infection-related hospitalization between 2007 and 2016 in the United States [ 16 ].…”
Section: Epidemiologymentioning
confidence: 99%